An innovative magnetic oxide dispersion-strengthened iron compound obtained from an industrial byproduct, with a view to circular economy - Tirado Gonzalez, J.G.; Reyes Segura, B.T.; Esguerra-Arce, J.; Bermúdez Castaneda, A.; Aguilar, Y.; Esguerra-Arce, A. (ELSEVIER, 2020)
Since the policy of Sustainable Production and Consumption has laid the basis for the world to begin its transition towards a circular economy, engineering has a moral responsibility to recycle industrial byproducts. This is currently done with calamine, which is a mill scale resulting from high temperature steel manufacturing. Although calamine is used in different ways, it could be given greater added value by subjecting it to processing by powder metallurgy. Therefore, the aim of this study was to obtain powder from iron with a core of enriched magnetite iron oxide, and to evaluate the effect of this iron oxide nucleus on the hardness and magnetic properties of the material after sintering. It was found that iron oxide acts as a reinforcement for iron (the highest achieved hardness was 77.7 ± 1.2 HRB) due, in part, to the coherency between phases, and confers a ferrimagnetic behavior to it. Therefore, this material has potential for use in magnetic applications at higher frequencies than current soft materials. © 2020 Elsevier Ltd. All rights reserved.

Dado que la política de Producción y Consumo Sostenible ha sentado las bases para que el mundo inicie su transición hacia una economía circular, la ingeniería tiene la responsabilidad moral de reciclar productos industriales subproductos. Actualmente esto se hace con calamina, que es una cascarilla de molino resultante de altas temperaturas. fabricación de acero. Aunque la calamina se utiliza de diferentes maneras, se le podría dar un mayor valor añadido sometiéndolo a procesamiento mediante pulvimetalurgia. Por lo tanto, el objetivo de este estudio fue obtener polvo de hierro con un núcleo de óxido de hierro enriquecido con magnetita, y evaluar el efecto de este hierro núcleo de óxido sobre la dureza y las propiedades magnéticas del material después de la sinterización. Se encontró que El óxido de hierro actúa como refuerzo del hierro (la dureza más alta alcanzada fue de 77,7 ± 1,2 HRB) debido, en en parte, a la coherencia entre fases, y le confiere un comportamiento ferrimagnético. Por tanto, este material tiene potencial para su uso en aplicaciones magnéticas a frecuencias más altas que los materiales blandos actuales. © 2020 Elsevier Ltd. Todos los derechos reservados.
Keywords: Economic development; Desarrollo económico; Steel; Acero; Magnetic amplifiers; Amplificadores magnéticos; Metals - Effect of high temperatures on; Metales a altas temperaturas; Metallic powder; Polvo metalico; Byproduct recycling; Reciclaje de subproductos; Powder metallurgy; Metalurgia de polvos; ReinfMetallic; Reinforcement; Reforzamiento; Circular economy; Economía circular